Generation and selection of anti-flagellin monoclonal antibodies useful for serotyping Salmonella enterica - Hiriart, Yanina (2013)
In developing countries, bacterial acute gastroenteritis continues to be an important cause of morbidity and mortality among young children. Salmonellosis constitutes a major cause of infectious enteritis worldwide, most of them associated to the consumption of contaminated food products. Traditionally, Salmonella has been classified in serovars based on varieties of O and H surface antigens. In the present work we generated and characterized a panel of anti-flagellin monoclonal antibodies (MAbs) in order to select antibodies useful for detecting the H surface antigen. Four different MAbs were obtained by somatic hybridization of splenocytes. We found two MAbs that recognised regions of flagellin conserved among different Salmonella serovars. Other two MAbs recognised structures restricted to Salmonella enterica sv. Typhimurium, being one of them suitable for agglutination tests. Using a diverse panel of S. enterica serovars with different H antigen varieties we confirmed that this MAb agglutinates specifically S. Typhimurium (antigenic formula: 4,12:i:1,2) or other serovars expressing flagellar factor i. In conclusion, we generated a valuable immunochemical tool to be used in simple assays for serotyping of epidemiologically relevant strains. The capacity to characterize specific strains and determine the primary sources of Salmonella contamination generate valuable information of the epidemiology of this microorganism, contributing to the improvement of public health.